Vocabulary learning through videos: captions, advance-organizer strategy, and their combination. Issue 3 (4th March 2022) - Teng, (Mark) Feng
Abstract: This study intended to examine L2 young learners' vocabulary learning (i.e. form, meaning, and use). The research design involved a 2 (advance-organizer strategy: present vs. absent) × 4 (caption type: glossed full captions, glossed keyword captions, full captions, keyword captions) between-subjects design. A total of 240 Chinese ESL primary school students were recruited and randomly and equally assigned to eight conditions. Findings revealed that captioned videos produced significant effects on learning regarding the three dimensions of vocabulary knowledge. Glossed full captions were found to be the most effective caption type. Administration of the advance-organizer strategy also resulted in better gains in learning form, meaning, and use than the absence of this strategy. The combination of the advance-organizer strategy and glossed full captions led to the best learning performance for each dimension of vocabulary knowledge. Relevant pedagogical implications, including use of the advance-organizer strategy and captions, are provided.